INNOVATION IN TOURISM - Fotima Saydullaeva , Ph.D; Ergashev Shokhrukh Jamolovich (European Science Publishing, 2024)
This article describes the importance of the tourism sector in the country's economy and the possibilities of its innovative processes in it, the article focuses on how much innovative concepts are needed in the field of Tourism and their study, based on world experiences and scientific approaches.
Keywords: innovation, tourism, types of innovation, services, personnel, transport.